Problems of governance in South Asia - Pai Panandiker, V. A., 1935-; Centre for Policy Research (New Delhi, India) (Dhaka : UPL, 2000)
Contributed articles
Includes bibliographical reference and index
Keywords: Democracy -- South Asia; South Asia -- Politics and government